Bluebeard - Metaphrog (Papercutz, 2020)
Presents a graphic novel that offers a feminist twist on a classic folktale. Eve and Tom grow up together, dreaming of traveling the world and exploring new lands. Their dream is soon shattered when Eve reaches womanhood and the mysterious Bluebeard chooses her to be his new wife. After they marry, Eve explores Bluebeard's castle in the enchanted woods, and uses a golden key to open a forbidden chamber. There she discovers a terrifying secret that threatens her life and the lives of those she loves.